Enhancement of Thermoelectric Properties in Cold Pressed Nickel Doped Bismuth Sulfide Compounds - Fitriani, Fitriani; Said, Suhana Mohd; Rozali, Shaifulazuar; Salleh, Faiz; Sabri, Mohd Faizul Mohd; Bui, Duc Long; Nakayama, Tadachika; Raihan, Ovik; Megat Hasnan, Megat Muhammad Ikhsan; Bashir, Mohamed Bashir Ali; Kamal, Farhan (Springer Verlag (Germany), 2018)
Abstract: Nanostructured Ni doped Bi2S3 (Bi2−xNixS3, 0 ≤ x ≤ 0.07) is explored as a candidate for telluride free thermoelectric material, through a combination process of mechanical alloying with subsequent consolidation by cold pressing followed with a sintering process. The cold pressing method was found to impact the thermoelectric properties in two ways: (1) introduction of the dopant atom in the interstitial sites of the crystal lattice which results in an increase in carrier concentration, and (2) introduction of a porous structure which reduces the thermal conductivity. The electrical resistivity of Bi2S3 was decreased by adding Ni atoms, which shows a minimum value of 2.35 × 10−3 Ω m at 300 °C for Bi1.99Ni0.01S3 sample. The presence of porous structures gives a significant effect on reduction of thermal conductivity, by a reduction of ~ 59.6% compared to a high density Bi2S3. The thermal conductivity of Bi2−xNixS3 ranges from 0.31 to 0.52 W/m K in the temperature range of 27 °C (RT) to 300 °C with the lowest κ values of Bi2S3 compared to the previous works. A maximum ZT value of 0.13 at 300 °C was achieved for Bi1.99Ni0.01S3 sample, which is about 2.6 times higher than (0.05) of Bi2S3 sample. This work show an optimization pathway to improve thermoelectric performance of Bi2S3 through Ni doping and introduction of porosity. Graphical Abstract: [Figure not available: see fulltext.].